Empowerment of Superior Free-Range Chicken Farmers Through a Participatory Action Research Approach to Strengthen Economic Independence - Suyatno Suyatno; Dewi Amanatun Suryani (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2026)
This Community Service activity aims to transfer knowledge about raising KUB chickens, including maintenance, coop management, feed management, disease prevention, product marketing, networking, and the application of technological innovations, to the community for the welfare and prosperity of the community. The activity was carried out in the Sleman region in collaboration with the Kampung Unggul Balitbangtan Sleman Utara. The method used in this program was a Participatory Action Research (PAR) approach, which involved the activities of planning, training, and technical guidance on KUB chicken maintenance, practical assistance in raising chickens, and the establishment of the Kampung Unggul Balitbangtan Mandiri Sejahtera Chicken Farmers Association. The results achieved were increased knowledge, the formation of an association, changes in husbandry patterns, and the active role of farmer members of the association in coordinating, discussing, and sharing ideas, innovations, and strategies in Kampung Unggul Balitbangtan chicken farming. This activity motivates the community to raise chickens, generating income for economic independence.